Bioaccumulation dynamics of a PCB low-level discharge in a riverine pathway downstream the release point - Maria, Gheorghe (Array, 2009)
Summary: The low biodegradability and high persistence in environment of POPs (persistent organic pollutants), and especially some of them such as PCBs (polychlorinated biphenyls), make their removal difficult and incomplete in conventional wastewater treatment plants (WWTP). A low-level quasi-continuous release of such pollutants in rivers,fluctuating around or beyond the admissible levels, is a quite common problem especially for discharges from large industrial plants. If the discharge contains a low-level pollutant load, such a problem apparently seems not to be so critical due to the fast pollutant dispersion over a relatively short section of the river pathway, i.e. over a few dozen meters downstream the WWTP release point. However, this problem can turn into a serious one if the pollutant is a POP, even for small concentrations in the WWTP effluent, due to their known high bioaccumulation capacity in biota and sediments. For this last case, the paper illustrates, by means of a relatively simple dynamic model and two case studies, how the dispersion and bioaccumulation critical zone of a PCB near the release point tends to move slowly downstream